Synthesis of Peracetylated β-D-Glucopyranosyl Thioureas from Substituted 2-Aminobenzo-1ʹ, 3ʹ-thiazoles - Nguyen Dinh Thanh (E-Journal of Chemistry)
Some peracetylated glucopyranosyl thioureas containing a heterocyclic ring system, benzo-1,3-thiazole have been prepared by the condensation reaction of tetra-O-acetyl-β-D-glucopyranosyl isothiocyanate and corresponding substituted 2-amino-(6-substituted)benzo-1,3-thiazoles. Investigated heating conditions showed that the solventless microwave-assisted method gave higher yields of these thioureas.